A Bibliometric Mapping of Outcome-Based Education and Its Epistemological Reconstruction from the Perspective of Ikhwan al-Ṣafā - Deni Suryanto (Global Education Journal, 2026)
The transformation of global higher education has adopted Outcome-Based Education (OBE) as the dominant paradigm that emphasizes competency measurability. However, the implementation of OBE in Islamic higher education faces serious challenges because the integration of character values is still formalistic and less transformative. This research aims to map the OBE discourse in global literature for the period 2020–2026 and reconstruct its epistemological foundations through the perspective of the Ikhwan al-Ṣafā to overcome the dichotomy between measurability and character transformation. Using a qualitative approach with a combination of bibliometric analysis of 200 Scopus indexed publications and conceptual reconstruction of Rasā'il Ikhwan al-Ṣafā, this study identifies the structure of discourse and formulates an integrative model. The findings show that the OBE literature is dominated by pedagogical-operational approaches (critical thinking, problem-based learning, project-based learning) with significant epistemological gaps—the absence of any connection with the terms epistemology or integration of knowledge. Meanwhile, the thought of the Brotherhood al-Ṣafā has very low academic visibility (only two publications), reflecting the epistemological disconnection between the classical Islamic intellectual tradition and modern curriculum theory. In response, this study formulated an Integrative Transformative Outcome-Based Education Model that synthesizes the principles of constructive alignment of OBE with the epistemology of the Brotherhood of al-Ṣafā through three innovations: Tripartite Constructive Alignment (instrumental, integrative, transformative), Authentic Spiritual Assessment Framework with calibrated rubrics, and curriculum sequencing based on progressive science hierarchy. This model offers concrete solutions to implement the Learning Outcomes of Graduates in a transformative manner, while enriching OBE into a humanistic accountability framework without sacrificing the principle of measurability, towards the formation of insān kāmil (perfect human beings) in Islamic higher education.